WIRELESS MAINTENANCE REPORTING SYSTEM (WMRS) - Wan Abd Ghani, Wan Non Zarina (Universiti Teknologi PETRONAS, 2007)
This project proposed how the mobile application can be implemented through the Wireless Application Protocol (W AP) for Wireless Maintenance Reporting System (WMRS) in UTP. WMRS enables user to send report to maintenance department by using their mobile phone. The report from the user can be transferred through the telephone service provider and then links it to the Internet and finally reaching the maintenance department server. This project was developed using J2ME technology as the main development platform. The outcome will focus on the implementation of WMRS in the UTP Maintenance Department. This project applied the Software Development Life Cycle (SDLC) which consists of planning phase, analysis phase, design, coding phase and implementing the testing through emulator.